The Contribution of Islam to planetary health - Omrani, Omnia El; Essar, Mohammad Yasir; Alqodmani, Lujain; Uakkas, Saad; Eissa, Mohamed; Jemilah, Mahmood *; Guinto, Renzo R (Elsevier, 2021)
The human ecosystem interface, embodied by the planetary health paradigm, is deeply embedded in all the world's religions and indigenous traditions.1 Yet, the ongoing planetary health discourse remains predominantly Western-orientated. As calls to decolonise health ensues, there is a need to explore and acknowledge other non-Western perspectives, such as those originating from the Islamic faith.2